A Case Study on Indian Youngsters: Internet Gaming Disorder and Internet Pornography Addiction - Prabhu, Anthony Kimton (International Journal of Computer Sciences and Engineering, 2018)
This research aimed to study the major psychological problems faced by Indian youngsters in internet addiction in connection with pornography and gaming.Also, this research discusses the economical benefits of the developed nations by the pornography industry. Hardcore pornography business and the vast, enormous and huge profit gained by the pornography movie makers, the porn-websites and the internet linkers which connect the link to the world people and marked as a mass destruction in the changing era of globalization. This case study clearly analyses the key element found throughout all internet related experiences: "The ability to maintain or heighten arousal with the click of a mouse of a finger". The research is conducted on the basis of an extensive literature search and review was performed utilizing a variety of sources. EBSCO collections like ERIC, LISTA, PsychARTICLES, PsychINFO and SocINDEX are referred for the researrch study. Internet related addictions are examined through ambiguosly titled papers performed by first author. Real incidents related to internet ponography addiction is taken as main consideration for analysing the case study. This research clearly shows that there is a significant level of development found in the internet pornography viewers group. This research clearly defines the source of addictions, effects and the recovery mechanism for psychological rebooting. This researchshows the importance of restrictions needed to stop the addition and other health issues. Apart from the internet pornography and addiction, internet gaming devlops the addictive nature of the younger generation groups. In order to reduce the side effects, the governemt has to implement strong rules in the dissemination of informtion through internet.